Integrasi Nilai-Nilai Islam dalam Media Pembelajaran Digital Berbasis Etnomatematika - Suwarji, Wahid Kurniawan; Faradiba, Surya Sari (Mandalika Mathematics and Educations Journal, 2025)
The advancement of digital technology in education demands learning media that are not only interactive but also rich in cultural and religious values. This study examines the significance of integrating Islamic values into ethnomathematics-based digital learning media, exploring how such an approach enhances students’ mathematical understanding and character development. A Systematic Literature Review (SLR) was conducted on publications from 2020 to 2025, applying rigorous inclusion, exclusion, and quality criteria. From an initial pool of 980 articles, five met the requirements and were analyzed in depth. The findings reveal that digital media such as emodules, ebooks, and digital comics embedded with Islamic values and local cultural elements are not only valid and engaging but also effective in improving conceptual understanding, student engagement, and moral formation. These results underscore the transformative potential of value-based and contextually grounded digital pedagogy.